2018
DOI: 10.1186/s13019-018-0727-4
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes of robot-assisted minimally invasive esophagectomy for esophageal cancer: a propensity score matched analysis

Abstract: BackgroundMinimally invasive esophagectomy (MIE) was shown to be effective in reducing the morbidity and was adopted increasingly. The robot-assisted minimally invasive esophagectomy (RAMIE) remains in the initial stage of application. This study evaluated its safety and feasibility by comparing short-term outcomes of RAMIE and video-assisted minimally invasive esophagectomy (VAMIE).MethodsBetween March 2016 and December 2017, 115 consecutive patients underwent RAMIE or VAMIE at our institute. The baseline cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 30 publications
5
67
1
Order By: Relevance
“…Although it has been reported that robot assisted recurrent laryngeal nerve chain lymph nodes lymphadenectomy is not safe [10], and has no advantage over open surgery in tumor prognosis [11], Chen j et al [12], Deng et al [13] and Li Xu el al. [14] ound that RAMIE has a de nite advantage in lymphadenectomy without increasing the risk of major postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that robot assisted recurrent laryngeal nerve chain lymph nodes lymphadenectomy is not safe [10], and has no advantage over open surgery in tumor prognosis [11], Chen j et al [12], Deng et al [13] and Li Xu el al. [14] ound that RAMIE has a de nite advantage in lymphadenectomy without increasing the risk of major postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference between the two groups with respect to the mean number of dissected lymph nodes (20 and 19, respectively; P = 0.420), duration of postoperative hospital stay (13.8 and 12.7 days, respectively; P = 0.548), overall rate of complications (37.0% and 33.3%, respectively; P = 0.776), rate of RLN injury (14.8% and 11.1%, respectively; P = 1.000), and rate of pneumonia (18.5% and 7.4%, respectively; P = 0.224). The authors concluded that the short‐term outcomes of RAMIE and VAMIE are comparable, and that RAMIS is safe and feasible . van der Sluis et al reported the short‐term and long‐term outcomes in 108 cases of RAMIE.…”
Section: Robotic Surgerymentioning
confidence: 99%
“…Mortality rate was 5% (one patient) as a result of a tracheoesophageal fistula . Propensity score matching analysis of RAMIE versus conventional video‐assisted minimally invasive esophagectomy (VAMIE) was reported in 2018 . Matching based on propensity scores produced 27 patients in each group.…”
Section: Robotic Surgerymentioning
confidence: 99%
“…A previous retrospective study from the same group showed that RAMIE can be performed with a high percentage of R0 radical resections, an adequate lymphadenectomy, an acceptable morbidity rate, and a low percentage (6%) of local recurrence after 5 years . On the contrary, the robot might also have some disadvantages, such as higher costs, more time‐consuming procedures, and the lack of tactile feedback . The proficiency gain curve might be even longer than for MIE although no large studies have been completed to support this assumption .…”
Section: Robotic Esophagectomymentioning
confidence: 99%
“…40 On the contrary, the robot might also have some disadvantages, such as higher costs, more time-consuming procedures, and the lack of tactile feedback. 44 The proficiency gain curve might be even longer than for MIE although no large studies have been completed to support this assumption. 45 In addition, these systems are unavailable for surgeons in all countries.…”
Section: Robotic Esophagectomymentioning
confidence: 99%